Fiscal Policy in India: Lessons and Priorities - Nirvikar Singh; T. N. Srinivasan (University of California, Economics Department, 2004)
This paper assesses India's current fiscal situation, its likely future evolution, and impacts on the economy. We examine possible reforms of macroeconomic policy (including fiscal, monetary and exchange rate policy) and broader institutional reforms that will bear on the macroeconomic situation. We also consider the political feasibility of possible reforms. We examine both medium and longer run scenarios, and fiscal sustainability and adjustment going beyond conventional government budget deficits, to include off-budget liabilities, both actual and contingent. We conclude with our assessment of reforms focused on improving the fisc.
Keywords: 330